Drama : between poetry and performance - Worthen, William B., 1955- 4 0 16; 5 (Chichester, West Sussex, UK; Wiley-Blackwell, 2010)
Describes an approach to reading drama that explores the link between text and performance, discussing examples by Shakespeare, Ibsen, Beckett, and Parks, and examining the elements that animate to a performance.
Includes bibliographical references (p. [216]-260) and index.
Adult;Adult.
Keywords: 2 -- 0; 6; History and criticism.;Technique. -- Drama;Drama;Theater. -- 20; 20; 2